Acceptability of Web-Based Multimodality Learning Media for Elementary School Teachers in West Java - Sutrisno, Lucky Taufik; Abidin, Yunus; Trie Kurniawan, Dede (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
The purpose of this research is to understand the extent to which teachers in West Java accept and use web-based multimodality learning media in their learning activities. This study involved elementary school teachers as research participants. The data was collected through surveys and interviews, which aimed to gain a comprehensive understanding of the views, attitudes, and experiences of teachers towards the use of web-based multimodal learning media. Factors such as technology knowledge, skills in using media, availability of infrastructure, institutional support, and teachers' personal preferences will be explored as factors influencing their acceptability to web-based multimodal learning media. Data analysis will be carried out to identify the factors that influence the level of acceptability of teachers towards web-based multimodality learning media. It is hoped that the findings of this study will provide insight into the level of acceptance by teachers of web-based multimodality learning media, as well as recommendations for the development and implementation of more effective learning media in elementary schools in West Java. Thus, this research has the potential to make a positive contribution to the development of education in West Java by strengthening the understanding of the acceptability of web-based multimodal learning media among elementary school teachers.